Students’ perception toward the use of open educational resources to improve writing skills - Dewi Zulaiha; Yunika Triana (Universitas Syiah Kuala, 2023)
Open educational resources (OER) can be used by English as a foreign language (EFL) students to improve their language skills, such as writing skills. The purpose of this study was to find out the students’ perception of using OER in improving their writing skills and to identify factors that affected their perception. A quantitative approach in the form of a descriptive survey design was used in this study. The study was conducted at Universitas Islam Negeri Raden Mas Said Surakarta, Indonesia, with 270 EFL students as the participants. The survey adopted two previous studies in which the data were analyzed using descriptive analysis, Pearson product-moment, and multiple regression analysis. The finding revealed that most students had positive perceptions toward using OER to improve their writing skills. Perceptions of using OER were influenced by interest factors (type of writing activity, type of learning writing delivery), experience factors (teaching effectiveness in the writing skills, cost of education), and from the participants, including gender. It is crucial to maximize the use of OER from different aspects, including quality, value, cognitive, affective, and course quality, particularly to increase their perception toward using OER in improving writing skills.